A new insight into casing shear failure induced by natural fracture and artificial fracture slip. (July 2022) - Meng, Hu; Ge, Hongkui; Yao, Yuan; Shen, Yinghao; Wang, Juchuan; Bai, Jie; Zhang, Zuodong
Highlights: Three slip modes of natural fracture and slip mechanism of artificial fracture were summarized. Considering the finite height and length of fracture, a new model was proposed to calculate the slip distance under three slip modes. The redistributed stress field of hydraulic fracturing and the friction characteristics of propped fracture were investigated. A real-time monitoring model was established to predict casing deformation. Abstract: Casing deformation is often encountered due to hydraulic fracturing in the unconventional reservoir. Analysis of 3D seismic, microseismic and logging data shows that the casing shear failure is the primary casing failure mode during hydraulic fracturing. The casing deformation is closely related to the fracture system near the wellbore, but the mechanism and law behind this phenomenon are not completely clear. The slip mechanism of the fracture system and the characteristics of casing deformation were investigated to prevent casing deformation and identify the fracture with large slip distance. Based on the Mohr-Coulomb and maximum circumferential stress theory, the slip mode of natural fracture and the slip mechanism of artificial fracture were analyzed, respectively. Then, two numerical models were established to calculate the slip distance with finite fracture height and corresponding casing deformation. Furthermore, a monitoring model of casing deformation was presented based on microseismic data and real-time injection parameters. The result shows three slip modes in the fracture system crossing wellbore under different fluid pressures, including shear-slip under low fluid pressure, open-slip under medium fluid pressure and propagation-slip under high fluid pressure. The slip distance is associated with fracture length, fracture height, fluid pressure in the fracture and fracture angle. Hydraulic fracturing not only activates natural fractures and faults but also causes the slip of artificial fractures created by hydraulic fracturing, which is responsible for the casing shear deformation after fracturing and during production. The greater the stress deflection angle, the longer and higher the artificial fracture, the more likely the casing deformation in the fracturing section. Therefore, the scale of artificial fracture should be controlled during hydraulic fracturing. This study will provide guidance for predicting fracture slip distance and casing deformation prevention.